Comparison of telbivudine and entecavir on the change of off- treatment eGFR after 3 years of treatment in non-cirrhotic chronic hepatitis B patients. Issue 1 (December 2017) - Lin, Yang-Sheng; Shih, Shou-Chuan; Wang, Horng-Yuan; Lin, Ching-Chung; Chang, Chen-Wang; Chen, Ming-Jen
Abstract Background The change of estimated glomerular filtration rate (eGFR) with off-treatment nucleos(t)ide analogues (NA) in chronic hepatitis B patients (CHB) is unclear. This study is aimed to evaluate the off-treatment eGFR after 3 years of therapy with telbivudine (LdT) or entecavir (ETV) and to assess predictive factors for eGFR improvement. Methods From January 2009 to December 2011, we identified NA-naïve patients who were at least 20 years of age diagnosed with compensated CHB. All patients received a 3-year NA treatment and 1 year off-treatment follow-up; the initial selection of patients for LdT or ETV treatment was at the physicians' discretion. An increase of more than 10% in eGFR from the baseline was identified as an improvement. The change of chronic kidney disease stages were recorded and compared with baseline at year 3 and year 4, respectively. Results This study included two groups consisting of 46 patients each (each with3 years of treatment with LdT or ETV). In LdT-treated patients, the mean eGFR increased from 94.3 ± 28.3 to 104.0 ± 31.2 mL/min/1.73 m2 in year 3 (p  = 0.01) and from 104.0 ± 31.2 to 104.0 ± 28.8 mL/min/1.73 m2 in year 4 (p  = 0.99). However, in ETV-treated patients, the mean eGFR decreased from 93.1 ± 26.1 to 85.5 ± 25.1 mL/min/1.73 m2 in year 3 (p  = 0.0009) and from 85.5 ± 25.1 to 87.7 ± 24.8 mL/min/1.73 m2 in year 4 (p  = 0.2). After a multivariate analysis, the predictors for the off-treatment eGFR improvement were the LdT treatment (odds ratio [OR], 3.97 (1.37–11.5), p  = 0.01) and pre-treated eGFR (OR, 0.98 (0.95–1.00), p  = 0.04). Conclusions At year 4, 48.8 and 21.3% patients had an improved eGFR from baseline in LdT and ETV patients, respectively. Telbivudine may have a protective renal effect that can last for one year after treatment in non-cirrhotic CHB patients without a virological breakthrough.